A Study of the Prevalence of Toxocariasis in Samarra City and its Relationship to Some Physiological Parameters - Hadi, Ammar Rassam; Shakir, Ohood Mozahim (Journal of Science in Medicine and Life, 2025)
This study was conducted from the beginning of September 2024 to June 2025 to investigate the incidence of toxocariasis in Samarra. Two hundred blood samples were collected from different age groups (15-50 years) from the Samarra General Hospital laboratory for both sexes. A questionnaire was also completed, including age, gender, occupation, residential location, and animal ownership. Results using the ELISA-TES IgG technique showed that the overall infection rate with toxocariasis was 9%. A relationship was also found between toxocariasis infection and age, gender, educational level, and animal ownership. The highest infection rate was recorded in the 45-41 age group, reaching 16.66%, while the highest infection rate among females was in the 45-41 age group, reaching 16.66%. Males in the 41–45 age range also had an infection rate of 11.11%, with the uneducated group having the highest rate at 33.33% and those who owned dogs and cats having the highest rate at 18.84%, while the group without dogs and cats had the highest rate at 3.81%. The statistical analysis's findings showed that there were significant differences at the p<0.05 and p<0.01 probability levels. On the other hand, the results of the current study showed a significant decrease ar p<0.01 in the levels of antioxidants, namely, catalase and superoxide dismutase, in samples positive for the ELISA test compared to the control group. Catalase levels in patients reached 9.9±1.57 pg/ml, compared to 15.26±1.62 pg/ml in the control group. Superoxide dismutase levels in patients reached 168.48±5.29 pg/ml, compared to 188.19±10.58 pg/ml in the control group.